2021
DOI: 10.1016/j.eja.2021.126288
|View full text |Cite
|
Sign up to set email alerts
|

Cocoa breeding must take into account the competitive value of cocoa trees

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Trebissou et al. (2021) reported several factors affecting cacao growth and productivity, such as the characteristics of neighbouring trees, resource limitations (soil nutrients and water), and physiological stress conditions (photoinhibition and shading effect), which can induce a competitive effect and/or affect production mechanisms. Wibaux et al.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Trebissou et al. (2021) reported several factors affecting cacao growth and productivity, such as the characteristics of neighbouring trees, resource limitations (soil nutrients and water), and physiological stress conditions (photoinhibition and shading effect), which can induce a competitive effect and/or affect production mechanisms. Wibaux et al.…”
Section: Discussionmentioning
confidence: 99%
“…(2021) reported that greater density of cacao trees increased the inter-tree competition (cacao vs. cacao; cacao vs. ATL): the closer the trees were to each other, the more they would try to grow taller to obtain more light. This competition between cacao trees occurred gradually, intensifying over time as resources were depleted (Trebissou et al., 2021). For Rijkers et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An updated evolutionary focus of crop yield in relation to plant-plant relations emphasizes kin selection and multi-level selection [85][86][87][88][89]. Empirical evidence supports the association between high yield per unit area and less competitive phenotypes in morphologically and physiologically diverse annual and perennial crops [90][91][92], including wheat (figure 5). In a collection of elite wheat CIMMYT 1 cultivars, removing or bending adjacent plant rows to relax competition with the focal central row showed a strong negative correlation between grain yield and response to reduced competition (figure 5a).…”
Section: Annual Crops and Fishes Respond To Environmental Variation Through Offspring Numbermentioning
confidence: 99%